Un Saltiri de Guillem II per a Monreale? sobre els orígens del Saltiri Anglocatalà de París - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2012)
The questions that this essay trays to answer are two: at the end af 12th century who could have commissioned this Psalter from the scriptorium of the Christ Church of Canterbury, a codex so luxurios and so influenced by the art of Sicily of Sicily? and why was it left unfinished? It might have been commissioned by King William II of Sicily for his cathedral of Monreale. His non-completion would by explained by his death and because of the events that followed his demise: the imprisoning of his widow Joan of England, her release by his brother Richard the Lionheart (who had to recognize Tancred as king of Sicily), the vicissitudes of the Third Crusade and, finally, in the context of the alliance between the English king and Alfons I of Catalonia (II of Aragon), the second marriage of Joan with the count of Toulouse. These events might have led the artists, deprived of sources of financing, to bring the codex to the Catalan-Aragon royal court and to work there in the decoration of the chapter house of Sigena, whose style and iconography are so closely related to the Psalter and to Monreale.